An Evaluation of the Impact of “Learning Design” on the Distance Learning and Teaching Experience - Clifton, Grace (International Review of Research in Open and Distributed Learning, 2017)
This paper evaluates the implementation of Learning Design on the production of a core FHEQ level 6 (QAA, 2008) unit of study at a UK distance learning institution. By comparing student (n=656) and tutor (n=42) survey data with questionnaire responses (n=9) from the unit of study’s core production team, this paper assesses the impact of incorporating the Open University Learning Design Initiative (OULDI) methodology into curriculum production by looking specifically at barriers and facilitators in the application of Learning Design and its impact on module development, delivery, and the resulting student and tutor learning experience. With a focus on developing and embedding Learning Design into the curriculum planning and production process, the paper explores how lessons learned from this experience have helped to guide and inform the future implementation of Learning Design into module and qualification level frameworks.